1994
DOI: 10.1152/ajpregu.1994.267.3.r747
|View full text |Cite
|
Sign up to set email alerts
|

Parasympathetic-mediated reflex salivation and vasodilatation in the cat submandibular gland

Abstract: The aim of the present study was to compare and characterize the secretory and vasodilator effects induced by chorda lingual nerve (CLN) stimulation (i.e., direct parasympathetic stimulation) and reflex parasympathetic stimulation in the submandibular gland (SMG) of sympathectomized cats. The increase in blood flow and salivary secretion in response to electrical stimulation of the central cut ends of the vagus and inferior alveolar nerves, as well as to stimulation of the CLN at a site approximately 5 mm dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…Parasympathetic stimulation is known to provoke salivary secretion strongly (21). Besides the role of parasympathetic nerves in saliva secretion, AQP5 is also known to play a major role in saliva secretion (35,43).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parasympathetic stimulation is known to provoke salivary secretion strongly (21). Besides the role of parasympathetic nerves in saliva secretion, AQP5 is also known to play a major role in saliva secretion (35,43).…”
Section: Resultsmentioning
confidence: 99%
“…The SMG was dissected on days 1,4,7,10,14,21, and 28 after bilateral CTD and weights were measured. Rats with no operation (0 day) were regarded as the control in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…These results suggest that secretion occurs subsequent to a delay period following the increase in [Ca 2 þ ] i . The involvement of blood flow in salivary secretion was suggested by the induction of salivation and the increase of blood flow in the SMG due to parasympathetic stimulation [49,50]. Monitoring blood flow in the SMG together with Ca 2 þ responses using a laser speckle imaging flowmeter demonstrated that mAChR stimulation-induced changes in blood flow were synchronized with the increase in [Ca 2 þ ] i and salivary secretion in the SMG.…”
Section: Intravital Imaging Of Ca 2 þ Dynamics In the Rat Submandibulmentioning
confidence: 99%
“…The Izumi group has reported that parasympathetic stimulation induces salivary secretion and increased blood flow [49,50]. In addition, taste stimuli such as sour, bitter, sweet, salty, and umami, also induce salivary secretion [51].…”
Section: Prospectivementioning
confidence: 99%
“…Agonist-induced fluid secretion from salivary glands in vivo is potentiated by cAMP-increasing agents (6,22,25), though the fluid secretion is reduced by the agents when doses of a muscarinic agonist and/or a cAMP-increasing agent are high (6). In addition, intravenous injection of cAMP-increasing agents induce a transient increase in glandular blood flow (25), whereas the vascular modulation around the salivary glands by parasympathetic nerve is postulated to be involved in the mechanism of the prominent salivation in vivo (15,24). Taken together, fluid secretion from salivary glands may basically depend on Cl Ϫ secretion, and other factors such as the increase in glandular blood flow also may affect the fluid secretion in in vivo experiments, especially at low doses.…”
Section: Discussionmentioning
confidence: 99%